Warming and CO2 Enhance Arctic Heterotrophic Microbial Activity - Vaqué, Dolors; Lara, Elena; Arrieta, Jesús M.; Holding, Johnna; Sà, Elisabet L.; Hendriks, Iris E.; Coello-Camba, Alexandra; Alvarez, Marta; Agustí, Susana; Wassmann, Paul F.; Duarte, Carlos M. (Frontiers in Microbiology, 2019)
Ocean acidification and warming are two main consequences of climate change that can directly affect biological and ecosystem processes in marine habitats. The Arctic Ocean is the region of the world experiencing climate change at the steepest rate compared with other latitudes. Since marine planktonic microorganisms play a key role in the biogeochemical cycles in the ocean it is crucial to simultaneously evaluate the effect of warming and increasing CO2 on marine microbial communities. Here, from water samples of a high-Arctic fjord (Svalbard), using an experimental microcosms approach, we examined changes in phototrophic and heterotrophic microbial abundances and processes (bacterial production and mortality), and viral activity in relation to warming and elevated CO2. We exposed a summer microbial plankton community to increased CO2 concentrations (135 – 2318 µatm) in three controlled temperature treatments (1°, 6° and 10°C). Results showed that bacterial production (BP) significantly increased with pCO2 at 6°C (R2 = 0.539, p = 0.015) and 10°C (R2 = 0.691, p = 0.003) temperature treatments. Lytic viral production was not affected by changes in pCO2 and temperature, while lysogeny increased significantly at increasing levels of pCO2, especially at 10ºC (R2 = 0.858, p = 0.02). Moreover, grazing rates showed a positive interaction between pCO2 and temperature. The averaged percentage of bacteria grazed per day was higher (19.56 ± 2.77% d-1) than the averaged percentage of lysed bacteria by virus (7.18 ± 1.50% d-1) for all treatments. Furthermore, the relationship among microbial abundances and processes showed that BP was significantly related to phototrophic pico/nanoflagellates abundance at the 1°C and the 6°C treatments, and BP triggers viral activity, mainly lysogeny at 6°C and 10°C, while bacterial mortality rates was significantly related to bacterial abundances at the 6°C. Consequently, a more acidic and warmer Arctic Ocean, as expected in the future, will show enhanced bacterial production and lysogeny and relative impact on grazers that will create changes in the carbon fluxes within the microbial food webs, leading to a reduced net community production and a weakening of the CO2 sink capacity of the Arctic plankton communities.